THE FUTURE OF CRYPTOVALUTA: AN ANALYSIS OF THE LITERATURE ON TRENDS AND INNOVATIONS IN THE DIGITAL AGE - Lucky Mahesa Yahya; Al-Amin (CV. Adiba Aisha Amira, 2024)
This research analyses the literature on the future of cryptovaluta with a focus on trends and innovations in the digital era. The results of the analysis show that cryptovaluta has great potential to transform various aspects of the digital economy, especially through decentralisation and the wider application of blockchain technology. The development of DeFi platforms, smart contracts, and NFTs are key innovations driving the growth of the crypto ecosystem. However, challenges such as inconsistent regulations, market volatility, and security issues remain the main obstacles that need to be overcome. Therefore, synergy between the government, tech industry, and crypto community is essential to create a balanced and sustainable framework, enabling cryptovaluta to contribute significantly in the digital economy of the future.